Myenteric Denervation Downregulates Galectin-1 and-3 Expression in Gastric Carcinogenesis - Estofolete, Cassia F.; Zucoloto, Sergio; Oliani, Sonia M. [UNESP]; Polli-Lopes, Ana Claudia; Gil, Cristiane D. (Springer, 2011)
Background This study evaluated the galectin-1 and -3 expression during N-methyl-N'-nitro-N-nitrosoguanidine (MNNG)-induced gastric carcinogenesis in denervated rat stomachs using benzalkonium chloride.Method Four experimental situations were evaluated: nondenervated and denervated stomachs without lesions and nondenervated and denervated stomachs with lesions. Sections of the pyloric region were stained with toluidine blue and incubated with mouse monoclonal anti-Gal-1 and rabbit polyclonal anti-Gal-3 for histopathological and immunohistochemical analysis, respectively.Result MNNG caused the development of benign and malignant epithelial lesions, which were more pronounced in nondenervated stomachs with lesions and accompanied by inflammatory cell-enriched stroma. By immunostaining, the epithelial cells, blood vessels, muscle layer, and myenteric plexus were Gal-1 and -3 positive. Gal-3 was also detected in the gastric crypts, mucus secretion, and fibroblasts of pyloric fragments. Development of lesions in denervated stomachs was associated with a significant decrease in Gal-1 and -3 expression in epithelial cells, mast cells, and neutrophil cytoplasm, compared with that of nondenervated stomach lesions (P < 0.01; P < 0.001; P < 0.001, respectively).Conclusion These results demonstrate that myenteric denervation downregulates endogenous Gal-1 and -3 expression, which might inhibit tumor development in this experimental model.
Keywords: Benzalkonium chloride; Galectin; Immunohistochemistry; Mast cells; MNNG; Neutrophil